Good governance: conventional and Islamic perspectives - Mohd. Adnan, Normala (Bangladesh Institute of Islamic Thought (BIIT), 2014)
Good governance as a concept introduced by the International Financial Institutions(IFIS) as a condition for granting loans to mostly less developed countries has become popular especially for international donors, international organisations, civil societies, and non-governmental organisations. Although most of them agree that good governance is essential to achieve development in various areas (Kura, 2008; Gonzales and Mendoza, 2004; Doig 1995; Loiu 2007), there is no consensus on what constitutes good governance.“This intrinsic open-ended quality, and inherent lack of specificity,” according to Doornbos (2003:375), generated a good deal of debate prompting multiple efforts toappropriate it and define it in a particular way. This article analyses the concept of good governance and its underlying values from liberal as well as Islamic perspectives. The way forward is perhaps to work on implementation of good governance based on context rather than leaving it for international institutions to decide on aspects of good governance deemed worthy for adoption. The paper argues that good governance principles from either liberal or Islamic perspective need not be abandoned on the ground of cultural diversity. These principles could be modified, altered, and improved to suit particular condition and as long as it promotes goodness to the society.